The clinical spectrum of chronic diarrhoea in children in a tertiary care hospital in Bangalore, India - Shenoy, Bhaskar; Dodderi, Sunil Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: In the developing world, chronic diarrhea is typically associated with serial enteric infections and malnutrition. There are many causes for chronic diarrhea and with better facilities these are being increasingly diagnosed in India. To study the clinical spectrum of chronic diarrhoea in children. in a tertiary care hospital in Bangalore Methods: This was a prospective observational study conducted at the Dept of Pediatrics, Dr.B.R.Ambedkar Medical College , Bangalore from April 2015 to April 2017. All the patients who presented with symptoms suggestive of chronic diarrhoea were enrolled for the study. 50 children fulfilling inclusion criteria were selected for the study. Results: Of 50 cases, 31(62%) showed cow milk protein intolerance (CMPI), 6 (12%) celiac disease, 5(10%) post infectious, 2(4%) glucose galactose intolerance, 1(2%) non-specific, 1(2%) cystic fibrosis, 1(2%) IBD, TB 1(2%) and 2(4%) lympangiectesia. In children below 2 years, cow milk protein intolerance was the most common cause of diarrhea whereas post infectious was the most common cause in 2-6 years age group and celiac disease in above 6 years of age group. Conclusions: Cow milk protein intolerance is the most common etiological factor. The incidence of celiac disease was the second most common cause after CMPI in the present study. The incidence of CMPI as a cause of chronic diarrhoea reduces as the age increases as seen in present study. The high incidence of celiac diseases may be due to referral to our institution by various peripheral hospitals when they could not diagnose after routine investigations.